El aprender, el saber y el enseñar: los problemas en el aula vida Estudio de Revisión Sistemática. - Gonzalo Tamayo Giraldo; Analía Verónica Losada (Perspectivas Metodológicas​)
Introduction: The analysis of how to know, how to learn, with what phases and due to what causes, are matters of psychology, or if you want epistemology, with direct intervention of pedagogy, pondering learning - knowing - teaching, axes that are at the same time present in each of the disciplinary problematizations.